2008
DOI: 10.1002/pros.20888
|View full text |Cite
|
Sign up to set email alerts
|

Bcl‐2 mediated modulation of vascularization in prostate cancer xenografts

Abstract: Together, these results demonstrate that Bcl-2 can regulate tumoral angiogenesis and lymphangiogenesis and suggest that therapy targeted at Bcl-2 expression, angiogenesis, and lymphangiogenesis may synergistically modulate tumor growth and confirm that Bcl-2 is a pivotal target for cancer therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 45 publications
2
9
0
1
Order By: Relevance
“…In vitro studies indicate that TEM8 has a role in various endothelial cell functions (4)(5)(6) and the extracellular domain of TEM8 can bind to extracellular matrix proteins (4, 7) as well as the protective antigen of anthrax toxin (8). Expression profiles for TEM8 include both research and clinical samples that provide strong evidence for the increased expression of TEM8 in tumor endothelial cells (3,7,9). In normal adult tissues, TEM8 expression is sporadic and found at lower levels than in tumor endothelium (7,10).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies indicate that TEM8 has a role in various endothelial cell functions (4)(5)(6) and the extracellular domain of TEM8 can bind to extracellular matrix proteins (4, 7) as well as the protective antigen of anthrax toxin (8). Expression profiles for TEM8 include both research and clinical samples that provide strong evidence for the increased expression of TEM8 in tumor endothelial cells (3,7,9). In normal adult tissues, TEM8 expression is sporadic and found at lower levels than in tumor endothelium (7,10).…”
Section: Introductionmentioning
confidence: 99%
“…The increased angiogenic potential correlated with increased serum levels of basic FGF (bFGF), IL-8 and MMP-9. 20 Subsequently, we evaluated human endothelial cells (human umbilical vein endothelial cells (HUVEC) and human dermal microvascular endothelial cells (HDMECs)) cultured in conditioned media from Bcl-2-overexpressing human prostate cancer cells. The conditioned media induced increased rates of proliferation and the expression of important antiapoptotic genes/proteins, possibly providing a survival advantage over endothelial cells grown in conditioned media from cancer cells with low Bcl-2 expression.…”
mentioning
confidence: 99%
“…The positive effect of the overexpression on mTORC1 activity indicates that up-regulation of these antiapoptotic proteins not only enhances cell survival but also stimulates mTOR-dependent proliferation in cancer cells. In support of this notion, it was found that up-regulation of Bcl-2 increased tumor cell proliferation and vascularization in prostate cancer xenografts (20), two events under control of mTORC1. Because translation of Bcl-2 and Bcl-X L is regulated by mTORC1-dependent activation of eIF4E (8), an enhanced mTORC1 activity is expected to increase the production of the two antiapoptotic proteins, which in turn is anticipated to further stimulate mTORC1 activity through the cross-talk.…”
Section: Discussionmentioning
confidence: 83%